Pegasus Bridge : June 6, 1944 - Ambrose, Stephen E. (New York : Simon and Schuster, 1985)
Gives an account of the first engagement of D-Day, the turning point of World War II.
D Company of the Ox and Bucks was the first company to go into action as a unit on D-Day. It also had the most demanding and important task of any of the thousands of companies involved in the assault. It carried out its task brilliantly. What follows is the story of how it was done. - Preface.
D-Day : 0000 to 0015 hours -- D-Day minus two years -- D-Day minus one year to D-Day minus one month -- D-Day minus one month to D-Day -- D-Day : 0016 to 0026 hours -- D-Day : 0026 to 0600 hours -- D-Day : 0600 to 1200 hours -- D-Day : 1200 to 2400 hours -- D-Day plus one to D-Day plus ninety -- D-Day plus three months to D-Day plus forty years -- Epilogue : The significance of Pegasus Bridge -- Appendix : Poett's orders to Howard.
Includes index.
Keywords: 1939-1945; World War, 1939-1945 -- Campaigns -- France -- Normandy; Military campaigns; History